4x + 2x = 68 - 219 : 216
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
https://hoc24.vn/cau-hoi/a-5x-2x-62-50b-5x-x-150-2-3c-6x-x-511-59-31d-5x-3x-36-334-124x-2x-68-219-216.2785429565572
a: \(\Leftrightarrow7x=35\)
hay x=5
b: \(\Leftrightarrow6x=78\)
hay x=13
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\Leftrightarrow6x=30\)
hay x=5
b: \(\Leftrightarrow6x=25+12-1=36\)
hay x=6
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\Leftrightarrow8x=108+12=120\)
hay x=15
b: \(\Leftrightarrow6x=60\)
hay x=10
![](https://rs.olm.vn/images/avt/0.png?1311)
`Answer:`
a. \(5x-[2x+1-\left(2x-3\right)-\left(4x+1\right)]\)
\(=5x-\left(2x+1-2x+3-4x-1\right)\)
\(=5x-2x-1+2x-3+4x+1\)
\(=\left(5x-2x+2x+4x\right)+\left(-3-1+1\right)\)
\(=9x-3\)
b. \(\left(-3x^2+2x-1\right)+\left(4x^2-2x+3\right)\)
\(=-3x^2+2x-1+4x^2-2x+3\)
\(=\left(-3x^2+4x^2\right)+\left(2x-2x\right)+\left(-1+3\right)\)
\(=x^2+2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) ( x2 - 3x )( x2 + 7x + 10 ) = 216
<=> x( x - 3 )( x + 2 )( x + 5 ) - 216 = 0
<=> [ x( x + 2 ) ][ ( x - 3 )( x + 5 ) ] - 216 = 0
<=> ( x2 + 2x )( x2 + 2x - 15 ) - 216 = 0 (1)
Đặt a = x2 + 2x
(1) trở thành a( a - 15 ) - 216 = 0 <=> a2 - 15a - 216 = 0 <=> ( a - 24 )( a + 9 ) = 0 <=> a = 24 hoặc a = -9
=> \(\orbr{\begin{cases}x^2+2x=24\\x^2+2x=-9\end{cases}}\Leftrightarrow\orbr{\begin{cases}x^2+2x-24=0\\x^2+2x+9=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}\left(x-4\right)\left(x+6\right)=0\\\left(x+1\right)^2+8>0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=4\\x=-6\end{cases}}\)
Vậy S = { 4 ; -6 }
b) ( 2x2 - 7x + 3 )( 2x2 + x - 3 ) + 9 = 0
<=> ( x - 3 )( 2x - 1 )( x - 1 )( 2x + 3 ) + 9 = 0
<=> [ ( x - 3 )( 2x + 3 ) ][ ( 2x - 1 )( x - 1 ) ] + 9 = 0
<=> ( 2x2 - 3x - 9 )( 2x2 - 3x + 1 ) + 9 = 0
<=> ( 2x2 - 3x - 4 - 5 )( 2x2 - 3x - 4 + 5 ) + 9 = 0
<=> ( 2x2 - 3x - 4 )2 - 16 = 0
<=> x( 2x - 3 )( 2x2 - 3x - 8 ) = 0
<=> x = 0 hoặc 2x - 3 = 0 hoặc 2x2 - 3x - 8 = 0
<=> x = 0 hoặc x = 3/2 hoặc x = \(\frac{3\pm\sqrt{73}}{4}\)
Vậy S = { 0 ; 3/2 ; \(\frac{3\pm\sqrt{73}}{4}\)}
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left[68-\left(197-216\right)\right]-\left[\left(-43\right)+168-216\right]\\ =\left[68-\left(-19\right)\right]-\left[\left(-43\right)-48\right]\\ =87+91\\ =178\)
[68−(197−216)]−[(−43)+168−216]=[68−(−19)]−[(−43)−48]=87+91=178
![](https://rs.olm.vn/images/avt/0.png?1311)
b: \(\Leftrightarrow32x^5+1-32x^5+1=2\)
=>2=2(luôn đúng)
a: \(\Leftrightarrow\left[\left(x-3\right)^2-\left(x+3\right)^2\right]\left[\left(x-3\right)^2+\left(x+3\right)^2\right]+24x^3=216\)
\(\Leftrightarrow-12x\left(2x^2+18\right)+24x^3=216\)
=>-216x=216
hay x=-1
![](https://rs.olm.vn/images/avt/0.png?1311)
g)\(2907\left(2x+1\right)=8721\)
⇔\(2x+1=3\)
⇔\(2x=2\)
⇔\(x=1\)
h)\(\left(4x-16\right):1905=60\)
⇔\(4x-16=114300\)
⇔\(4x=114316\)
⇔\(x=28579\)
i)\(23+3x=5^6:5^3\)
⇔\(23+3x=5^3\)
⇔\(23+3x=125\)
⇔\(3x=102\)
⇔\(x=34\)
k)\(219-7\left(x+1\right)=100\)
⇔\(7\left(x+1\right)=119\)
⇔\(x+1=17\)
⇔\(x=16\)
tôi cũng muốn giải bài này !!